Simple and fast orotracheal intubation procedure in rats - Tomasello, Giovanni; Damiani, Francesco; Cassata, Giovanni; Palumbo, Vincenzo Davide; Sinagra, Emanuele; Damiani, Provvidenza; Bruno, Antonino; Cicero, Luca; Cupido, Francesco; Carini, Francesco; Lo Monte, Attilio Ignazio (Acta Biomedica Atenei Parmensis, 2016)
Abstract: Introduction: Endotracheal intubation in the rat is difficult because of the extremely small size of anatomical structures (oral cavity, epiglottis and vocal cords), small inlet for an endotracheal tube and the lack of proper technical instruments. Material and Methods: In this study we used seventy rats weighting 400–500 g. The equipment needed for the intubation was an operating table, a longish of cotton, a cotton tip, orotracheal tube, neonatal laryngoscope blades, KTR4 small animal ventilator and isoflurane for inhalation anaesthesia. Premedication was carried out by medetomidine hydrochloride 1 mg/mL; then, thanks to a closed glass chamber, a mixture of oxygen and isoflurane was administered. By means of a neonatal laryngoscope the orotracheal tube was advanced into the oral cavity until the wire guide was visualized trough the vocal cords; then it was passed through them. The tube was introduced directly into the larynx over the wire guide; successively, the guide was removed and the tube placed into the trachea. Breathing was confirmed using a glove, cut at the end of a finger, simulating a small balloon. Results: We achieved a fast and simple orotracheal intubation in all animals employed. Conclusions: We believe that our procedure is easier and faster than those previously reported in scientific literature.